A FINANCIAL TRANSFORMATION OF MSMES THROUGH DIGITALIZATION IN MADIUN REGENCY - Ayu Rahmawati, Labbaika Dwi; Nursulistyo, Emy Dwi; Arista, Denty; Tiara Murti, Galuh; Saputra, Zaim Arif Eko; Seto, Bayu (LPPM ITB AAS Indonesia Surakarta, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Madiun Regency face significant challenges in financial management, which is still predominantly manual, resulting in low accountability and difficulties in accessing financing. This community service activity aims to transform MSME financial governance through digitalization by implementing and providing assistance in the use of the MOFIN UMKM (Modern Finance) website. The implementation method consists of three stages: (1) initial observation through the distribution of questionnaires to MSMEs; (2) development of the MOFIN UMKM website as a financial reporting platform; and (3) intensive assistance in the use of the MOFIN UMKM website. This program is a collaboration between academics and the Madiun Regency Government. Evaluation results from 31 post-assistance questionnaires show that MSMEs greatly benefited from the digitalization of financial reporting using the MOFIN UMKM website. The platform simplifies transaction recording and the preparation of financial reports. The active collaboration between academia and the local government in developing and implementing the MOFIN UMKM website has proven to be an effective solution for modernizing MSME financial reporting in Madiun Regency.